Multiple Myeloma A Quick Reflection on the Fast Progress - Hajek, Roman (IntechOpen, 2013)
This book does not provide a comprehensive overview of Multiple Myeloma but a collection of chapters with in-depth information of distinct hot topics in the diagnostic, research and therapeutic fields. The dynamics of testing new drugs for multiple myeloma treatment in clinical trials is breathtaking. Scientific discoveries have uncovered complicated pathogenesis of multiple myeloma; complicated reactions to treatment lead to the creation of super cocktails. Curability of multiple myeloma is a question that is being discussed by the entire professional myeloma world. Improvement of prognosis is a fact which is most important from a patient's perspective. We believe that this book could be of interest to medical professionals specializing in hematooncology, researchers, as well as many others.